2023
DOI: 10.1186/s12920-023-01516-9
|View full text |Cite
|
Sign up to set email alerts
|

De novo variation in EP300 gene cause Rubinstein-Taybi syndrome 2 in a Chinese family with severe early-onset high myopia

Abstract: Background Rubinstein-Taybi syndrome (RSTS) is characterized by distinctive facial features, broad and often angulated thumbs and halluces, short stature, and moderate-to-severe intellectual disability, classified into two types RSTS1 (CREBBP-RSTS) and RSTS2 (EP300-RSTS). More often, the clinical features are inconclusive and the diagnosis of RSTS is established in a proband with identification of a heterozygous pathogenic variant in CREBBP or EP300 to confirm the diagnosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…However, variations in these genes may only explain a small part of patients with eoHM and the genetic defects for most patients with eoHM are yet unknown and may be caused by variants in unknown novel genes. Some studies showed that eoHM may occur associated with other ocular or systemic diseases and so associated with the responsible genes, such as LPR2 causing Donnai-Barrow syndrome with eoHM [14] and EP300 causing Rubinstein-Taybi syndrome 2 with eoHM [15].…”
Section: Introductionmentioning
confidence: 99%
“…However, variations in these genes may only explain a small part of patients with eoHM and the genetic defects for most patients with eoHM are yet unknown and may be caused by variants in unknown novel genes. Some studies showed that eoHM may occur associated with other ocular or systemic diseases and so associated with the responsible genes, such as LPR2 causing Donnai-Barrow syndrome with eoHM [14] and EP300 causing Rubinstein-Taybi syndrome 2 with eoHM [15].…”
Section: Introductionmentioning
confidence: 99%
“…EoHM can be further classi ed into simple (nonsyndromic) and syndromic types, the latter associated with ocular abnormalities such as hereditary retinal diseases (IRDs) or systemic abnormalities [4]. Recent studies suggest a signi cant association between eoHM and hereditary retinal [4]diseases (IRDs) or systemic syndromes, with mutations in genes responsible for IRDs found in approximately one-fourth of eoHM cases [14,15]. This study utilizes whole exome sequencing (WES) to analyze pathogenic gene variants in patients exhibiting the initial signs of eoHM.…”
Section: Introductionmentioning
confidence: 99%